Analisis Struktur Naskah Drama Anggun Nan Tongga Karya Wisran Hadi - Afdal Putra; Muhammad Ismail Nasution (Departemen Bahasa dan Sastra Indonesia dan Daerah, 2023)
The type of researchi conductedi by researchers is literary research using descriptive methods. Descriptive methode is a method of findingi facts with the righti interpretation of the pbject of research. The purpose of the descriptive method is to make description, pictures or drawings of data and facts in systematic, factual and accurate manner. The data collectioni technique was carried out in several stages: (1) Read and understand the drama script Anggun Nan Tongga as a whole carefully and repeatedly. (2) Marking the dialogue according to the research problem. This study aimsi to describe the structural elementsi, the functions of the structural elements, and the relationship between structural elements in the drama script AnggunI Nan Tongga by Wisran Hadi. From the result of the discussion found in the previous section, it can be concluded that the analysis of the structure of the play Anggun Nan Tongga has three stages, namely (1) Analyzing the structural elements of the play Anggun Nan Tongga. (2) Describe the function of the structural elements of the play Anggun Nan Tongga. (3) Describei the relationshipi between the elements of the Anggun Nan Tongga drama script structure.